2014
DOI: 10.1016/j.compstruct.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tow-drop gaps on the damage resistance and tolerance of Variable-Stiffness Panels

Abstract: This paper presents an experimental study of the effects of tow-drop gaps in Variable Stiffness Panels under drop-weight impact events. Two different configurations, with and without ply-staggering, have been manufactured by Automated Fiber Placement and compared with their baseline counterpart without defects. For the study of damage resistance, three levels of low velocity impact energy are generated with a drop-weight tower. The damage area is analyzed by means of ultrasonic inspection. Results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…However, the test results showed that an open hole has a stronger negative influence than that of a gap singularity. The effects of impact and compression after impact were also studied, experimentally and numerically [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the test results showed that an open hole has a stronger negative influence than that of a gap singularity. The effects of impact and compression after impact were also studied, experimentally and numerically [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The angle between adjacent courses determines the shape and size of the resulting gaps and overlaps [22]. Within the transitions zones of gaps and overlaps (transition from pristine to defective laminate) fiber angle deviations and fiber waviness may occur [48,51,69,[71][72][73][74][75][76]. The imperfection size is the determining factor for the formation of fiber waviness [48,56,57,71,77].…”
Section: Type Iv-gap and Overlapmentioning
confidence: 99%
“…Some research groups [56,57,72,78,79] quantify the effects of gaps and overlaps on material and laminate level. Faló et al [73,74] experimentally investigate the damage tolerance of unconventional laminates. They find no statistically significant influence of gaps and overlaps on the strength of laminates with impact damage under compression.…”
Section: Type Iv-gap and Overlapmentioning
confidence: 99%
“…Moreover, the staggering of plies can largely reduce the effect of defects in un-notched VSP composites [27]. The influence of defects on the impact damage tolerance of steered laminates was found to be relevant only for very low impact energies [28].…”
Section: Fiber-steering For Improved Composite Performancementioning
confidence: 99%